2021
DOI: 10.1063/5.0048012
|View full text |Cite
|
Sign up to set email alerts
|

Velocity and density measurements in forced fountains with negative buoyancy

Abstract: In fluid mechanics, fountains take place when a source fluid is driven by its own momentum into a surrounding ambient fluid, and it is counterbalanced by buoyancy. These phenomena are largely encountered in nature and human activities. Despite the numerous studies on the subject, few experimental data are available about the internal structure of turbulent fountains. Here, we present a set of laboratory experiments with the aim to (i) get direct velocity and density measurements of fountains in a controlled en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
2
1
0
Order By: Relevance
“…A similar finding has been reported by Addona et al. (2021), who analysed the turbulent kinetic energy, the velocity skewness and the Reynolds stresses of the fluctuating velocity in a turbulent forced fountain. They found that the turbulent kinetic energy is maximum at (where is the steady height of the fountain), suggesting that the maximum production of turbulence takes place near the base of the fountain top, where the inner flow meets the pulsating fountain top.…”
Section: Introductionsupporting
confidence: 88%
See 2 more Smart Citations
“…A similar finding has been reported by Addona et al. (2021), who analysed the turbulent kinetic energy, the velocity skewness and the Reynolds stresses of the fluctuating velocity in a turbulent forced fountain. They found that the turbulent kinetic energy is maximum at (where is the steady height of the fountain), suggesting that the maximum production of turbulence takes place near the base of the fountain top, where the inner flow meets the pulsating fountain top.…”
Section: Introductionsupporting
confidence: 88%
“…They also presented a statistical description of a turbulent fountain as consisting of a potential core surrounded by a growing shear region; a cap region of large-scale pulsating flow where generation of turbulence due to buoyancy is significant; and finally an annular counterflow region that is akin to a buoyant plume. A similar finding has been reported by Addona et al (2021), who analysed the turbulent kinetic energy, the velocity skewness and the Reynolds stresses of the fluctuating velocity in a turbulent forced fountain. They found that the turbulent kinetic energy is maximum at z/z ss ∼ 1 (where z ss is the steady height of the fountain), suggesting that the maximum production of turbulence takes place near the base of the fountain top, where the inner flow meets the pulsating fountain top.…”
Section: Introductionsupporting
confidence: 86%
See 1 more Smart Citation